The Correlation Between Family Support with The Quality of Life of School-Age Children with Thalassemia - Astarani, Kili; Yuli F.W, Laurensia; Sutik; Taviyanda, Dian; David Richard, Selvia (Babali Publisher, 2024)
Introduction: Thalassemia is a severe disease affecting many school-aged children, characterized by symptoms such as weakness and paleness due to low hemoglobin levels. These children often require routine blood transfusions, which can lead to several side effects impacting their quality of life. Generally, the quality of life for school-aged children with thalassemia is lower than that of their healthy peers. Family support is one factor that can influence the quality of life of children with thalassemia. This study investigated the relationship between family support and quality of life in school-aged children with thalassemia at Immanuel Way Halim Hospital, Bandar Lampung.Methods: The research design was descriptive-analytic with a cross-sectional approach. The sample included all school-aged thalassemia patients in the Edelweiss Hospital room at Immanuel Way Halim, totaling 28 respondents. The sampling technique used was purposive sampling, with inclusion criteria being school-aged thalassemia patients (ages 7 to 18 years) who could communicate well. Data analysis was conducted using the Chi-square test.Results: The results indicated that 19 respondents (67.9%) had positive family support, and 14 (50%) had a high quality of life. Statistical analysis showed a p-value of 0.027 (<0.05).Conclusion: There is a significant relationship between family support and the quality of life of children with thalassemia in the Edelweiss Hospital room at Immanuel Way Halim, Bandar Lampung.